Design of Flying Wing Tail Sitter Contra-Rotating Propeller VTOL Sky Swift V1.0 UAV (Journal of Informatics Education and Research, 2025)
This research presents the design, optimization, and validation of SkySwift V1.0, a new hybrid flying-wing tailsitter Unmanned Aerial Vehicle (UAV) designed specifically for disaster management and rapid response missions. SkySwift V1.0 combines vertical takeoff and landing (VTOL) capability with efficient fixed-wing cruise performance. The SkySwift V1.0 design addresses some of the most pressing limitations of traditional UAV configurations, including transition instability, limited payload capacity, and short duration. The airframe is a blended wing-body, with forward-swept wings and a modular airframe configuration. In addition, the SkySwift V1.0 uses a contra-rotating pusher configuration designed for improved thrust balance and redundancy. To evaluate aerodynamic performance, a multi-fidelity approach was used to commence development through the use of vortex lattice methods (XFLR5) and then vis-à-vis Reynolds-averaged Navier–Stokes (RANS) solutions (ANSYS Fluent). The airframe was evaluated with respect of winglet configurations (i.e., split-scimitar vs. canted), airfoil selection (S1223 for VTOL configuration and E423 for cruise configuration), and the dynamic stability of the transition. Early results indicated lift-to-drag ratios (L/D) improved by more than 2:1, induced drag reductions of more than 15% with optimized winglets, and the successful maintenance of control authority during transition phases. This research demonstrates the potential for an adaptable UAV platform that could autonomously operate in complex and hazardous environments with potential uses in payload delivery and situational awareness.